2020
DOI: 10.1038/s41433-019-0759-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and complications of iris-fixated intraocular lenses in cases with inadequate capsular support and complex ophthalmic history

Abstract: Background To report the indications, visual outcomes, and intra-operative and post-operative complications of iris-sutured posterior chamber intraocular lens (IOL) in eyes with inadequate capsular support and complex ocular history. Methods A chart review and data analysis of eyes that underwent iris fixation of posterior chamber (PC) IOL for correction of aphakia, dislocated and subluxed IOLs, ectopia lentis, and IOL exchange. Data included clinical risk factors, asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…49,114 In addition to the risk of on-going iris chafing, the most common complications with this technique include pupil ovalization, lens dislocation, glaucoma and retinal detachment. [124][125][126]…”
Section: Iris-sutured Pc Iolsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,114 In addition to the risk of on-going iris chafing, the most common complications with this technique include pupil ovalization, lens dislocation, glaucoma and retinal detachment. [124][125][126]…”
Section: Iris-sutured Pc Iolsmentioning
confidence: 99%
“…While posterior iris fixation of the IOL is a viable option in these patients, there are significant technical challenges in the use of the McCannel suture technique, given an enlarged anterior segment, poorly dilating pupil and sutures with needles of limited length 49,114 . In addition to the risk of on‐going iris chafing, the most common complications with this technique include pupil ovalization, lens dislocation, glaucoma and retinal detachment 124–126 …”
Section: Surgical Managementmentioning
confidence: 99%
“…To date, most studies have reported small case series of short follow-up periods for combined TPPV and IF-PCIOL in the same sitting after removal of subluxated lenses or IOLs with lensectomy or IOL explant respectively. [6][7][8][9][10][11][12] Therefore, we aim to report a case series of the 1-year surgical outcomes and safety profile of TPPV and IF-PCIOL implantation for subluxated cataracts and IOLs.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques of sutureless fixation of haptics in the transscleral tunnel are associated with the risk of complications associated mainly with damage of the haptics. Haptic kink, breakage, dislocation or slippage and less frequently IOL dislocation have been described in literature [8], [9]. Each of the complications lead to a decrease in quality and acuity of vision.…”
Section: Introductionmentioning
confidence: 99%
“…A more serious complication was corneal oedema, requiring DSAEK, which was observed in 7.5% of a group of 135 eyes. Other complications, observed in less than 10% of all cases were: vitreous haemorrhage, hyphema, macular oedema and retinal detachment [2]- [9].…”
Section: Introductionmentioning
confidence: 99%